Chitosan Supplementation may Improve the Digestive Physiology and Health of Captive Leiothrix lutea. (December 2015) - Le, Wang; Ting-Ting, Liao; Xi-Long, Wang; Gui-Ping, Yuan; Shi-Bin, Yuan
We investigated the effects of supplemental chitosan on digestibility of feed nutrients, intestinal histology and digestive enzyme activity in the pancreas, duodenum and jejunoileum in Leiothrix lutea. Sixty-four adult birds were randomly allotted to one of four dietary treatments (basal diet supplemented with 0%, 0.1%, 0.5% and 1% chitosan). The experiment lasted for 30 days, of which the last 4 days involved metabolic experiments. Compared with the control group, the addition of 0.5% chitosan enhanced the apparent metabolism rate of dry matter, metabolisable energy, crude fat and phosphorus, and decreased apparent metabolism rate of calcium; crude protein was unaffected. Compared with the control group, the villous height of the duodenum and ileum supplemented with 0.5% chitosan increased by 12.11% and 15.03%, while the crypt depth in the duodenum deepened by 6.48%. Supplemental chitosan decreased lipase and amylase activities; trypsin and chymotrypsin activities increased first and then decreased as the level of chitosan increased. These data suggest that dietary chitosan (0.5%) may improve the digestive physiology of L. lutea in captivity by increasing the apparent metabolic rate of most nutrients, improving intestinal health and enhancing digestive enzyme activity.